Perancangan Aplikasi Berteknologi Barcode Untuk Pengelolaan Perpustakaan Berbasis Multiuser Di SMA Negeri 1 Mranggen Demak - Siswanto Siswanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2018)
Mranggen Demak State High School Library is a work unit formed with the decision of an authorized official to serve the needs of school residents to the books in Mranggen Demak State High School. In this school library the library management is still conventional by taking notes in the big books. Services to library members are ineffective and unsatisfactory because it takes a long time to find the books they will borrow on every bookshelf available and look at notes in the big books. The slow preparation of the report so that the development of the library is less attention. Seeing these conditions the author tries to provide alternatives by making applications that can facilitate data processing and improve the efficiency of time and cost that has been in the school library. At this writing, the application made is a multiuser-based barcode technology application with a life cycle system development method. The system is designed using Microsoft Visul Basic 6.0 with a SQL Server 2000 database so that the implementation is in the form of a ready-to-use application system that is implemented in a library room. Application management of multiuser-based barcode technology is expected to be able to solve the problems that exist in the SMA Negeri 1 Mranggen Demak Library because in this system the data is processed centrally in one database so that data is not only recorded in the big books that have been happening.